Foldings and grazings of tori in current controlled interleaved boost converters. (11th March 2013) - Giaouris, Damian; Banerjee, Soumitro; Stergiopoulos, Fotis; Papadopoulou, Simira; Voutetakis, Spyros; Zahawi, Bashar; Pickert, Volker; Abusorrah, Abdullah; Al Hindawi, Mohammed; Al‐Turki, Yusuf
SUMMARY Interleaved boost converters (IBCs) are used when energy conversion is required at high current levels. Such converter systems may undergo various nonlinear phenomena which can affect their performance adversely. In this paper, we study an IBC and demonstrate the first instability through a Neimark–Sacker bifurcation, resulting in a torus. An analysis based on the calculation of the monodromy matrix reveals that the torus has a rather strange form as the complex Floquet multipliers that became unstable have a real value close to −1. We show that further variation in a parameter can result in novel nonlinear phenomena where the torus itself folds and grazes a switching manifold, resulting in a 'wobbling' of the closed loop that represents the torus in discrete time. Numerical and analytical results validate our work. Copyright © 2013 John Wiley & Sons, Ltd.